Internalization of Environmental Externalities: Processing Palm Waste into Renewable Energy - Prof. Dr. Ir. Eka Intan Kumala Putri M.Si; Rifdah Utami Hasna Nadhifah (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2024)
In 2021, the European Union issued a lawsuit at the World Trade Organization (WTO) regarding the halt in palm oil exports. The European Union Parliament considers the palm oil industry in Indonesia to be one of the triggers of deforestation, degradation and other environmental problems. Based on data from the Central Statistics Agency in 2019, the area of ??oil palm plantations in Indonesia reached 14.3 million hectares and the area of ??oil palm plantations in the Province was 2.7 million hectares (Yanti and Lestari 2020). This is based on the high demand for oil from palm oil and its derivative products which has an impact on negative externalities due to the extraction process carried out. The Palm Oil Fresh Fruit Bunches (FFB) production process produces many products such as Crude Palm Oil (CPO) and Palm Kernel Oil (PKO). Crude palm oil (CPO) production plays an important role in both the local-global environment and socio-economics. In this case, Internalization of Externalities is needed to minimize dirty oil (palm oil waste) which is detrimental to third parties from the management process carried out. Based on the case study of Panyabungan Village, the externality value for liquid palm oil waste is IDR 146,194,433,- after internalizing the externalities, we get a Total Economic Value (TEV) of IDR 627,602,359,- with the liquid waste and solid waste aspects of palm oil in three locations namely; Jambi, Bengkulu and Kalimantan. As a preventive form of assessing externalities, economic and environmental studies also include a SWOT analysis to develop strategies for the sustainability of Palm Oil in Indonesia.